2018
DOI: 10.1177/1526602818802581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Techniques for Isolated Left Subclavian Artery Revascularization During Thoracic Endovascular Aortic Repair in Zone 2

Abstract: Management of the left subclavian artery (LSA) during thoracic endovascular aortic repair (TEVAR) has generated considerable debate, especially in terms of prevention of stroke and spinal cord ischemia (SCI). 1-8 The most recent guidelines advocated selective LSA revascularization in most thoracic aortic pathologies. 9-11 Although different techniques and approaches are in use, 12-15 there has been no prior study or analysis comparing open LSA revascularization with other options such as chimney grafts (CGs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 59 publications
2
29
0
2
Order By: Relevance
“… 6) In fact, there are only four studies exclusively comparing carotid–subclavian bypasses or subclavian–carotid transposition to chimney or periscope–sandwich grafts for LSA debranching. 8 , 15 17) Table 4 demonstrates their results along with studies that examined either open or parallel graft-based LSA debranching only. 2 , 4 , 6 , 9 , 18) A former study from the reporting institution also described results of periscope–sandwich grafts for LSA debranching, but as only some of the patients were included into the presented cohort, their results were not used for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6) In fact, there are only four studies exclusively comparing carotid–subclavian bypasses or subclavian–carotid transposition to chimney or periscope–sandwich grafts for LSA debranching. 8 , 15 17) Table 4 demonstrates their results along with studies that examined either open or parallel graft-based LSA debranching only. 2 , 4 , 6 , 9 , 18) A former study from the reporting institution also described results of periscope–sandwich grafts for LSA debranching, but as only some of the patients were included into the presented cohort, their results were not used for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…As in our study, statistical differences were neither detected for strokes, mortality, or reintervention rate. 8 , 15 17) …”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis published in 2016 [15], which compared retrospective studies, they found a stroke rate of 2.2% to 5.8% for patients with left subclavian artery revascularization and from 7.8% to 9.1% In those who did not revascularize, with respect to spinal cord ischemia, a rate of 2.7% was reported for those patients with revascularization and 4.3% for those patients without revascularization of the left subclavian artery, without statistical significance for these results, but with a trend in favor of revascularization of the left subclavian artery.…”
Section: Zonementioning
confidence: 99%
“…Factors related to stroke and spinal ischemia include the duration of the procedure, the degree of underlying aortic disease, device navigation and release, the number of prostheses used in aortic repair, occlusion below T10, insufficiency renal and female sex [15][16][17][18]. Mortality from revascularization and non-revascularization of the left subclavian artery in hybrid procedures is similar, 3.1% to 4.3% respectively.…”
Section: Zonementioning
confidence: 99%
“…Dentro de la literatura, encontramos estudios donde se busca la preservación del flujo en la arteria subclavia 7,8 , e igualmente comparación entre la realización de bypass carótido-subclavio vs. manejo endovascular, sin encontrar diferencias significativas 9 , sin embargo, no hay mucha evidencia en el manejo con chimeneas del resto de los vasos supraaórticos 5,[10][11][12] . En la poca evidencia encontrada se observa que el manejo de zonas de anclaje más proximales se reserva a patología del arco aórtico y aorta ascendente 5,11,13,14 .…”
Section: Introductionunclassified